2012
DOI: 10.1128/aac.05530-11
|View full text |Cite
|
Sign up to set email alerts
|

First Human Isolate of Salmonella enterica Serotype Enteritidis Harboring bla CTX-M-14 in South America

Abstract: eWe studied a clinical isolate of Salmonella enterica serotype Enteritidis showing resistance to oxyiminocephalosporins. PCR analysis confirmed the presence of bla CTX-M-14 linked to IS903 in a 95-kb IncI1 conjugative plasmid. Such a plasmid is maintained on account of the presence of a pndAC addiction system. Multilocus sequence typing (MLST) analysis indicated that the strain belongs to ST11. This is the first report of bla CTX-M-14 in Salmonella Enteritidis of human origin in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
(36 reference statements)
2
11
0
3
Order By: Relevance
“…In this regard, we recently reported the occurrence of bla CTX-M-14 in an isolate of Salmonella enterica serovar Enteritidis, encoded in a similar plasmid [40]. Additionally, in our continent, IncI1 plasmids harboring bla CTX-M-14 and bla CTX-M-19 (both belonging to group 4 in the CTX-M family) have already been described in E. coli strains in our country and in Bolivia [14,36].…”
Section: Discussionsupporting
confidence: 57%
“…In this regard, we recently reported the occurrence of bla CTX-M-14 in an isolate of Salmonella enterica serovar Enteritidis, encoded in a similar plasmid [40]. Additionally, in our continent, IncI1 plasmids harboring bla CTX-M-14 and bla CTX-M-19 (both belonging to group 4 in the CTX-M family) have already been described in E. coli strains in our country and in Bolivia [14,36].…”
Section: Discussionsupporting
confidence: 57%
“…Jin and Ling 36 reported the presence of bla-CTX-M genes on 62 kb, 70 kb, and 92 kb harbored by S. enteritidis and S. typhimurium from Hong Kong, while Mshana et al 31 found a 231 kb plasmid to be responsible for the carriage of bla-CTX-M-15 gene among S. enterica isolates from Tanzania. In a study carried out by Bado et al 37 in Uruguay, where the first description of bla CTX-M-I gene cluster in S. enteritidis was reported, a 195 kb plasmid was incriminated as a vector. In Germany, Fischer et al 38 reported the transferability of blaCTX-M-15 among Salmonella isolates from horse and swine through 95 kb IncF and Inc1I plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…The strains were recovered from the following origins (the number of strains is in parentheses): chickens (11), beef (5), sheep (2), and a turkey (1). They harbored different variants of ESBL genes (number of strains), including (1). and blashv-5 (1) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%